Assessment of functional, coordination and power fitness of 7-8 form boys - Ivashchenko O.V; Yermakova T.S (Kharkov National Pedagogical University, 2015)
Purpose: determination of informative indicators of 7-8 form boys' motor and functional fitness. Material: in the research 24 pupils of 7 th form and 35 pupils of 8 th form participated. For assessment of functional and motor fitness test of Shtange, Genchi, Serkin and motor tests were conducted. Results: Analysis witnesses that be results of testing between boys of 7 th and 8 th dorm there are statistically confident differences by most of indicators (p<0.05:0.001). By functioning of respiratory and blood circulation systems 7-8 form boy pupils were assessed as healthy-not trained. Conclusions: structural coefficients of canonic discriminant function witness that the function is connected to the largest extent with variables. So, substantial difference between 7 th for pupils and 8 th form pupils was observed in condition of motor abilities: speed-power, coordination of movements and strength itself.